Visually-based Knowingly Illusory Presence and Picture Display - Voltolini, Alberto (Phenomenology and Mind, 2018)
The aim of this paper is twofold. First, I want to show how picture perception is specifically presentational, hence specifically perceptual, by suitably reinterpreting Richard Wollheim’s conception of seeing-in. Picture perception is such for it only ascribes the presence of the picture’s subject in its content, but not in its mode, for the subject is visually known not to be there: thus, it amounts to a knowingly illusory perceptual experience of such a presence. Second, I want to show how this presentational specificity does not prevent the picture itself from being properly presentational of the properties that are ascribed, within its perception, to its subject: the design properties of the picture’s vehicle present the perceivable properties ascribed to the picture’s subject just as the sensory features of a standard perceptual experience present the perceivable properties of its object.